Peningkatan Keterampilan Guru dalam Pembuatan Media Pembelajaran Berbasis Android Bermuatan Soal AKM - Moh Mahfud Effendi; Hendarto Cahyono; Siti Khoiruli Ummah; Rusi Ulfa Hasanah (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to describe improving teacher skills in making Android-based learning media containing AKM questions. The method of the service program was carried out with pre-activity procedures, implementation of activities which included training and mentoring, and evaluation. The instrument for evaluating this activity used a questionnaire and was analyzed descriptively. This service's results showed that teachers could create Android-based learning media. The questionnaire results distributed to teachers as training participants were the Kodular application used to develop media that was easy to use and attractive in terms of appearance. The results of the questionnaire given to students after the trial were that students were interested in learning to use Android-based media because it was practical and easy to access at any time. In addition, through Android-based media, it was easy for students to answer AKM-type questions, so as many as 84% of students passed the AKM.